A Circle Dancing Song 2 - G.yu lha (World Oral Literature Project, 2009)
The fifty one audio and nine video files in this collection include: villages’ life stories, circle-dancing songs and performance, local history, folk tales, and interviews from Siyuewu Village, Puxi Township, Rangtang County, Aba Tibetan and Qiang Autonomous Prefecture, Sichuan Province, China.
This is a circle dancing song.
Keywords: Oral Literature; Oral Tradition; Linguistic Anthropology; Lavrung; Siyuewu; Amdo Tibetan; Village history; Folk tales